Daya Tarik Pasar Tradisional terhadap Konsumen - Wigiyanti Wigiyanti; Agustina Nicke Kakiay (LITERATUS, 2022)
The modern market is growing and changing very quickly. The emergence of various types of non-traditional markets can increase competition between the regular market and the contemporary market. The increasing popularity of modern shopping places compared to traditional markets is supported by changes in people's behavior. Each market must have its own charm to attract visitors. The purpose of this study is to find out how market attractiveness affects consumer preferences. The results of the analysis show that Traditional Markets are attractive for several reasons, including the variety of goods, prices of goods, and public facilities. Giant Superdome is also interesting, because of the convenience factor, variety of goods, price of goods, physical condition of the market, and market facilities. Both markets are mostly accessible by road, however the island of roads separating the lanes makes them less accessible, especially for consumers on the other side of the market. It can be concluded from the analysis of several articles that there is a relationship between market attractiveness and consumer preferences, with modern markets being preferred over traditional markets